Sustainable Development as a Legal Argument for the Global South - Permana, Rizky Banyualam; Juwana, Hikmahanto; Afriansyah, Arie (Indonesian Journal of Law and Society, 2024)
The concept "trade and sustainable development" is often associated with and can be traced to the Global North. However, there is a paradigmatic change in the employment of the concept as legal argument in the context of trade dispute. This paper especially focuses on the Indonesia – Raw Minerals dispute. In the WTO dispute concerning Indonesia's raw minerals export ban, the European Union (EU) challenged Indonesia over its export restrictions and Domestic Processing Requirement (DPR). Rather than invoking Article XX(g) of the GATT 1994, which addresses the conservation of exhaustible natural resources—a common approach among WTO members—Indonesia chose to rely on Article XX(d) of the GATT 1994. This article justifies trade restrictions necessary to fulfill WTO-compliant obligations, including the imperative to promote sustainable development in the minerals sector. Although Indonesia ultimately lost the dispute, its use of sustainable development as a defensive strategy merits examination. This paper analyses the narrative techniques Indonesia employed to defend its export restrictions and DPR measures in the WTO proceedings. Drawing on the “Neo” New Haven School perspective which emphasises critical perspective on international law, the paper views the dispute through the lens of “international law as language.” This approach posits that international law is intertwined with political realities and serves as a communicative tool for international actors to engage within the global community. Ultimately, this paper argues that Indonesia's invocation of "sustainable development" reflects legal mimicry, demonstrating how terminology originating from the Global North is now being appropriated as a legal argument by the Global South to empower them.